Mitral Annular Disjunction in Mitral Leaflet Prolapse: Prevalence, Clinical Profile and Echocardiographic Features at Tertiary Cardiac Care Centre, Rawalpindi - Virk, Mutahir Abbas; Siddique, Muhammad Bilal; Iqbal, Usman; Ahmed, Sajjad; Shiram, Syed Ali; Ahmed, Adeel; Shahzad, Syed Khurram; Sana, Ayesha; Yousaf, Hussain (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the prevalence of Echocardiographically-recognizable Mitral Annular Disjunction in patients of Myxomatous Mitral Valve Disease/Mitral Leaflet Prolapse.Study design: Analytical Cross sectional .Place & Duration of study: Armed Forces Institute of Cardiology/National Institute of Heart Disease (AFIC/NIHD),Rawalpindi Pakistan from Jul 2021 to Sep 2021.Methodology: A total (n=45) diagnosed patients of Myxomatous Mitral Valve disease, were included through non-probability consecutive sampling. Mitral Annular Disjunction (MAD) was assessed by 2D TTE imaging as the distance between the point of insertion of the posterior leaflet into the left atrial wall (upper boundary of the disjunction) and the link between the left atrium and the left ventricle myocardium (lower border of the disjunction)at end-systole in parasternal long axis view. A distance equal to or greater than 2mm was used as a threshold for diagnosing the presence of MAD. The data analysis was done with the help of computer software programme SPSS version 24.Results: Total number of patients were 45 patients with males being 32 (71.11%) while females being 13 (28.88%), with a mean age of 30.24 + 5.21 years. MAD was present in 26 (57.8%) of the patients with mean length of 2.88mm + 2.77 mm. Patients with MAD had more chest pain, palpitations and dyspnoea than those without MAD. Mitral regurgitation was more severe in patients with MAD than without. The MAD severity correlated with the presence of Non Sustained Ventricular Tachycardia.Conclusion: MAD is not an uncommon finding in patients having myxomatous mitral valve disease/mitral valve prolapse........